The Error Analysis and its Nature Found in Foreign Language Learners’ Writing - Dwi Rahayu (LPPM Press, 2014)
It is a kind of library research which aims at revealing: (1) the definitions of error analysis;(2) the sources of error; (3) error taxonomy and linguistic category; (4) relevant research oferror analysis. The strategy of this research is modified from George (2008: 66) through thefollowing phases: (1) motivation or assignment; (2) topic selection; (3) research questions(brainstorming); (4) research plan (strategy); (5) reference works & databases (tools &tactics); (6) sources; (7) evaluation; (8) drafting & revising. Error is one of the lerners’interlanguage prosess where the learners make unnecessary items to be included or evenommit the necessary items. Those issues are virtually unique to note and being ongoingresearch that has never ended. This research is carried out to have more affinity for thestudents’ error so then the teachers can be responsive in giving his or her policy in Eglishteaching strategy priority. Based on the relevant research findings, the frequent errors madeby the students are in using participles and past costumes (the highest error is past simple) itmay be caused of the frequent usage of the basic grammar used by the students. It impliesthat drilling on the frequent error is a must and becomes priority to focuse.